(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
This paper is focused on economic cycle on the labor market in the entire national economy of the Czech Republic and in particular in the construction industry of Czechia. Authors use indicators of price level development. Analysis applies methods of the Hodrick–Prescott filter, Kalman filter and Stochastic trend to improve the informative value and credibility of reached conclusions. Phases of economic cycle on the labor market can be verified by comparison with the actual development of unemployment and gross domestic product. Special attention is given to unstable periods on the labor market, and we focus on determining reasons for their existence, their duration and manifestation. The analysis revealed negative gaps in the period of economic transformation but there were periods with positive unemployment gaps in the years 2007 and 2008 too. We used the development in the last period to predict the development in the near future. This ad hoc estimate is compared with model estimate made on an extended time series up to the end of the year 2018.